Предмет: Математика, автор: azimovashirin

помогитеееее, очень надо

Приложения:

Ответы

Автор ответа: krampus777
0

Ответ:

u)y = x {}^{ - 4}  \\ y =  - 4x {}^{ - 5}  \\ y =  -  \frac{4}{ {x}^{5} }  \\ v)y =  (3x - 4) {}^{ - 5}  \\ y =  {g}^{ - 5}  \times 3x - 4) \\ y =  - 5 {g}^{ - 6}  \times 3 \\ y =  - 5(3x - 4) {}^{ - 6}  \times 3 \\ y =  -  \frac{15}{(3x - 4) {}^{6} }  \\ w)y =  \sqrt[3]{(2 - 3x {)}^{2} }  \\ y = (2 - 3) {}^{ \frac{2}{3} }  \\  y =  {g}^{ \frac{2}{3} }  \times (2 - 3x) \\ y =  \frac{2}{3} g {}^{ -  \frac{1}{3} }  \times ( - 3) \\ y =  \frac{2}{3}  \times (2 - 3x {)}^{ -  \frac{1}{3} }  \times ( - 3) \\ y =  -  \frac{2}{ \sqrt[3]{2 - 3x} }  \\ x)y =  \cos(2 {x}^{2} + 4x )  \\ y =  \cos(g)  \times 2 {x}^{2}  + 4x \\ y =  -  \sin(g)  \times (2 \times 2x + 4) \\ y =  -  \sin(2 {x }^{2}  + 4x)  \times (4x + 4)

Решение выше

Надеюсь помог)

Похожие вопросы
Предмет: Алгебра, автор: dfsdfsdfrfgrefrefce
Предмет: Алгебра, автор: CHAPPYCHAP